Surface lime and silicate application and crop production system effects on physical characteristics of a Brazilian Oxisol - Castro, G. S.A.; Crusciol, C. A.C. [UNESP]; Rosolem, C. A. [UNESP]; Calonego, J. C. [UNESP]; Brye, K. R. (CSIRO Publishing, 2017)
This work aimed to evaluate the effects of crop rotations and soil acidity amelioration on soil physical properties of an Oxisol (Rhodic Ferralsol or Red Ferrosol in the Australian Soil Classification) from October 2006 to September 2011 in Botucatu, SP, Brazil. Treatments consisted of four soybean (Glycine max)-maize (Zea mays)-rice (Oryza sativa) rotations that differed in their off-season crop, either a signal grass (Urochloa ruziziensis) forage crop, a second crop, a cover crop, or fallow. Two acid-neutralising materials, dolomitic lime (effective calcium carbonate equivalent (ECCE)≤90%) and calcium-magnesium silicate (ECCE≤80%), were surface applied to raise the soil's base saturation to 70%. Selected soil physical characteristics were evaluated at three depths (0-0.1, 0.1-0.2, and 0.2-0.4m). In the top 0.1m, soil bulk density was lowest (P<0.05) and macroporosity and aggregate stability index were greatest (P<0.05) in the forage crop compared with all other production systems. Also, bulk density was lower (P<0.05) and macroporosity was greater (P<0.05) in the acid-neutralising-amended than the unamended control soil. In the 0.1-0.2-m interval, mean weight diameter and mean geometric diameter were greater (P<0.05) in the forage crop compared with all other production systems. All soil properties evaluated in this study in the 0.2-0.4-m interval were unaffected by production system or soil amendment after five complete cropping cycles. Results of this study demonstrated that certain soil physical properties can be improved in a no-tillage soybean-maize-rice rotation using a forage crop in the off-season and with the addition of acid-neutralising soil amendments. Any soil and crop management practices that improve soil physical properties will likely contribute to sustaining long-term soil and crop productivity in areas with highly weathered, organic matter-depleted, acidic Oxisols.
Keywords: aggregation; liming; no-tillage system; silicate application; soil structure.